CASE STUDY: SPRAIN ANKLE FASE AKUT DENGAN PENERAPAN MANUAL LYMPHATIC DRAINAGE MASSAGE DAN NEUROMUSCULAR TAPING UNTUK MENGURANGI NYERI DAN OEDEM - Yose Rizal; Nova Relida Samosir (Jurnal Ilmiah Fisioterapi, 2024)
Lateral Sprain Ankle is an injury that occurs due to excessive stretching (overstretching and hypermobility) or trauma to the lateral ligament complex, due to sudden inversion and plantar flexion forces during exercise or physical activity. The aim of this research is to determine the effectiveness of Manual Lymphatic Drainage Massage and Neuromuscular Taping (NMT) to reduce pain and swelling. This research uses the Case Study method. The sample for this study was a 16 years old male who was given physiotherapy intervention in the form of a combination of Manual Lymphatic Drainage Massage and Neuromuscular Taping (NMT) which was carried out at the ADA Physiotherapy Clinic Pekanbaru with physiotherapy procedures 6 times over 2 weeks. Pain values ​​are measured using the Visual Analog Scale (VAS), while swelling is measured using a measuring tape (meterline). After 6 treatments, it was found that the pain score was reduced from 7 to 3 on the Visual Analog Scale (VAS), swelling circumference from 54.8 cm to 53.2 cm using the Figure of Eight technique. The results of this study show that the application of Manual Lymphatic Drainage Massage and Neuromuscular Taping (NMT) can reduce pain and swelling in Lateral Sprain Ankle conditions.